IMPROVING THE METHODOLOGY OF DEVELOPING STUDENTS' METALINGUISTIC COMPETENCES (American Journal of Interdisciplinary Research and Development, 2022)
The development of metalinguistic awareness is an essential component of enhancing learners’ methodology . Enhancing students' metalinguistic understanding of their different skill successes is essential. Therefore , it is recommended to apply a range of techniques for increasing metalinguistic awareness, such as word recognition, syntactic understanding, and vocabulary recognition exercises. Not only metalinguistic is essential for improving methodology, but also it is crucial for all levels of education. Numerous studies have demonstrated that effective learners self-regulate their learning processes using metacognitive information and strategies. Being aware of metalinguistic lets mankind grasp the significance of the messages they read or hear. Additionally, to the fact that they may greatly favour career prospects, these two benefits have an impact on learners' social status.